Towards the Development, Maintenance, and Standardized Phenotypic Characterization of Single‐Seed‐Descent Genetic Resources for Common Bean. Issue 5 (18th May 2021) - Cortinovis, Gaia; Oppermann, Markus; Neumann, Kerstin; Graner, Andreas; Gioia, Tania; Marsella, Marco; Alseekh, Saleh; Fernie, Alisdair R.; Papa, Roberto; Bellucci, Elisa; Bitocchi, Elena
Abstract: The optimal use of legume genetic resources represents a key prerequisite for coping with current agriculture‐related societal challenges, including conservation of agrobiodiversity, agricultural sustainability, food security, and human health. Among legumes, the common bean ( Phaseolus vulgaris ) is the most economically important for human consumption, and its evolutionary trajectories as a species have been crucial to determining the structure and level of its present and available genetic diversity. Genomic advances are considerably enhancing the characterization and assessment of important genetic variants. For this purpose, the development and availability of, and access to, well‐described and efficiently managed genetic resource collections that comprise pure lines derived by single‐seed‐descent cycles will be paramount for the use of the reservoir of common bean variability and for the advanced breeding of legume crops. This is one of the main aims of the new and challenging European project INCREASE, which is the implementation of Intelligent Collections with appropriate standardized protocols that must be characterized, maintained, and made available, along with the related data, to users such as breeders and researchers. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Characterizing common bean seeds for seed trait descriptors Basic Protocol 2 : Bean seed imaging Basic Protocol 3 : Characterizing bean lines for plant trait descriptors specific for common bean Primary Seed Increase